Oxoisoaporphine nanocapsules for treating depression - Sobarzo, Sanchez Eduardo; Cebey, Lopez Miriam; Fontenla, Jose Angel; Otero, Espinar Francisco; Torres, Labandeira Juan J.; Grillo, Renato; Fernandez, Fraceto Leonardo (Instituto Nacional de Propriedade Industrial (INPI), 2013)
Oxoisoaporphine nanocapsules for treating depression. Nanocapsule systems are described that incorporate compounds of formula I or II that allow controlled, timed release of said compounds. Also described are the production method, the pharmaceutical compositions and the use for preparing a drug.
Nanocapsulas de oxoisoaporfinas para el tratamiento de la depresion
Processo: ES2402132B1
Processo: WO2013050637
Número de publicação: ES2402132 (B1)
Número de publicação: ES2402132 (A1)